Comparison of polyflavonoids in bayberry tanning effluent and commercial bayberry tannin: prerequisite information for vegetable tanning effluent recycling. (20th January 2016) - Teng, Bo; Jian, Xiaoyun; Gao, Yanping; Chen, Wuyong
Abstract: Recycling system is capable to minimize the serious environmental issues in leather making. It also has the advantage of reducing chemical consumption and providing an efficient way to decrease the cost of leather manufacture. High chemical oxygen demand, bio-chemical oxygen demand and microbial toxicity are all considered as the characters of vegetable tanning effluent, however, only a few recycling technologies were developed. In this study, bayberry tanning effluent was obtained with a commercial bayberry tannin through a common vegetable tanning process, then the polyflavonoids in the bayberry tanning effluent and commercial bayberry tannin were characterized with Fourier translation infrared spectrum, matrix-assisted laser desorption/ionization time of flight mass spectrometry, nuclear magnetic resonance, gel permeation chromatography and an elemental analysis. The results showed that the flavanol subunit in the polyflavonoids of the bayberry tanning effluent was the same with the commercial bayberry tannin, however the differences of the polyflavonoids between the bayberry tanning effluent and commercial bayberry tannin were presented in the aspect of stereochemistry, molecular weight as well as the quantity of sulfonic acid group. Polyflavonoid in the bayberry tanning effluent was composed of cis isomers, while both cis and trans stereoisomers were found in the commercial bayberry tannin. Average molecular weight of the bayberry tanning effluent was 1130 Da, in contrast to an obviously higher value in the commercial bayberry tannin (2292 Da). Meanwhile, higher sulfonic acid group content was presented in the bayberry tanning effluent. These structural differences were deduced in accordance with the diversity of collagen binding activities of the polyflavonoids. For the first time, the polyflavonoids in vegetable tanning effluent were characterized, meanwhile, the structural differences between the polyflavonoids in tanning effluent and commercial tannin were found. The results can be applied on the development of the vegetable tanning effluent related recycling technology. Highlights: The bayberry effluent was composed of polyflavonoids with lower molecular weight. The bayberry effluent was composed of polyflavonoids with cis -form isomers. Both cis and trans stereoisomers were found in the commercial bayberry tannin. Higher sulfonic acid group content was presented in the bayberry effluent.